Strengthening SMEs competitiveness and performance via industrial internet: Technological, organizational, and environmental pathways - Shaofeng Wang; Mengjia Gao; Hao Zhang (Humanities & Social Sciences Communications)
Abstract The industrial internet acts as a crucial accelerator for driving enterprise digital transformation and plays a vital role in enhancing performance and competitiveness. However, our understanding of how small and medium-sized enterprises (SMEs) leverage the industrial internet to improve their performance and competitiveness remains limited. This study developed a “Digital transformation paths chain” framework to shed light on the key factors that drive SMEs to adopt the industrial internet and its influence on performance and competitiveness. Data from 314 Chinese SMEs were collected and analyzed using fsQCA and PLS-SEM to examine this model. Our findings highlight the positive impact of industrial internet adoption on enterprise performance and competitive advantage. The results highlight that technology, organization, and environment (TOE) drive industrial internet adoption. Industrial internet adoption positively impacts enterprise performance and competitive advantage through integration, application, and drive. This study offers valuable insights for businesses, policymakers, and other stakeholders engaged in digital transformation initiatives through the industrial internet.